Concentration of biopetrol synthesized from oleic acid through catalytic cracking using zeolite as catalyst - Nurul Liana, Abd Rahman (2009)
Oleic acid is one of the major fatty acid in vegetable oil. In this research, zeolite catalysts are used over the conversion of oleic acid into isooctane as the future biopetrol in a heating mantle at atmospheric pressure. The main purposed of studies is to improve the concentration of isooctane using catalytic cracking method. The effect of various amount of Zeolite catalyst at 1g, 5g, 10g and 20g and various dilution factor of isooctane to hexane at 1%, 5%, 10% and 20% are studied over the yield of biopetrol at 98o C. Gas chromatography is used for the qualitative and quantitative analysis of the samples. Backward calculation is applied to calculate the actual concentration of isooctane in the distilled oleic acid. The maximum yield of desired isooctane obtained at 20g of catalyst and dilution of 20% isooctane to hexane is recorded at 7.89%. Experimental works has successful show that catalytic cracking is greater in conversion than thermal cracking.